The Role of Technology in Contemporary Education: A Comparative Analysis of Benefits and Challenges - Jain, Chandra Prakash (Journal of Educational Research and Policies, 2026)
In recent years the learning process witnessed massive changes especially in the methods used in teaching and instruction. Knowledge is no longer limited to traditional tools such as pens and books. Many of today’s jobs require talents and skills that are highly related to technology. The rapid evolution and growth of the information technology has transformed learners into digital learners Therefore, specialists in the educational sector have endorsed the use of technology in teaching. It requires teachers to integrate technology into their educational approaches. So, their technological knowledge and skills play a significant role in this effective integration. From this perspective, this study investigates the role of technology in modern education, comparing it with traditional teaching methods. Through an analysis of secondary sources, the paper examines the benefits, such as enhanced learning opportunities and improved engagement, and challenges, including distractions and accessibility issues. It aims to analyse the impact of technology on educational methods, comparing traditional and modern approaches, and assessing the advantages, challenges, and future implications of technology integration in education. Findings suggest that while technology significantly enhances education, it is essential to balance traditional and modern approaches to optimize learning outcomes. All the data used in this study comes from secondary sources. Information was gathered from several sources, including journal papers, published dissertations, online textbooks. These resources help in defending the topic of the research.